Pengaruh Stres dan Rewards terhadap Kepuasan Freelancer Gen Z: Peran Motivasi - Welim Hansen; Erna Listiana; Efa Irdhayanti; Ilzar Daud; Dody Pratama Marumpe (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The advancement of digital technology has driven significant transformations in the employment landscape, marked by the emergence of new occupational roles such as freelance content creators—professions that are particularly appealing to Generation Z. Despite operating independently and with high levels of flexibility, these freelance workers remain subject to complex psychosocial work dynamics, including job stress, rewards, motivation, and job satisfaction. This study aims to empirically investigate the influence of job stress and rewards on job satisfaction, while examining the mediating role of motivation within the context of digital freelancers. Employing a quantitative research design, data were collected through an online questionnaire distributed to 220 Gen Z freelance content creators in Indonesia. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, facilitated by the SmartPLS 4 software. The results indicate that job stress exerts a significantly negative effect on both motivation and job satisfaction, whereas rewards have a significantly positive effect on these variables. Furthermore, motivation was found to partially and significantly mediate the relationship between job stress, rewards, and job satisfaction. These findings underscore the critical importance of affective dimensions in shaping the occupational well-being of freelancers in the digital era. The main contribution of this study lies in its extension of the theoretical framework surrounding non-traditional work dynamics, as well as its practical implications for the development of career management and well-being strategies tailored to platform-based freelance workers.